2006
DOI: 10.1038/sj.onc.1209329
|View full text |Cite
|
Sign up to set email alerts
|

Cbl escapes Cdc42-mediated inhibition by downregulation of the adaptor molecule βPix

Abstract: The Pix/Cool proteins are involved in the regulation of cell morphology by binding to small Rho GTPases and kinases of the Pak family. Recently, it has been shown that bPix/Cool-1 associates with the ubiquitin ligase Cbl, which appears to be a critical step in Cdc42-mediated inhibition of epidermal-growth-factor-receptor (EGFR) ubiquitylation and downregulation. Here we show that the SH3 domain of bPix specifically interacts with a prolinearginine motif (PxxxPR) present within the ubiquitin ligase Cbl and Pak1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
1
37
2
Order By: Relevance
“…Further studies on Src-transformed cells revealed that Cool-1 phosphorylation status modulates their migration and invasive activity [16]. In addition, previous studies (using overexpression analyses) reported that a complex of Cdc42 and Cool-1 is required to inhibit c-Cbl [11,30]. In contrast, our studies demonstrate the importance of Cool-1 and its inhibition of c-Cbl in at least a subset of naturally occurring GBMs, one of the most deadly human cancers.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Further studies on Src-transformed cells revealed that Cool-1 phosphorylation status modulates their migration and invasive activity [16]. In addition, previous studies (using overexpression analyses) reported that a complex of Cdc42 and Cool-1 is required to inhibit c-Cbl [11,30]. In contrast, our studies demonstrate the importance of Cool-1 and its inhibition of c-Cbl in at least a subset of naturally occurring GBMs, one of the most deadly human cancers.…”
Section: Discussioncontrasting
confidence: 52%
“…In comparison, disruption of c-Cbl by inhibitory proteins has received much less attention. Previous studies on human tumors showed that Cdc42 knockdown in breast cancer cells reduces proliferation and migration and enables reductions in EGFR levels (apparently in a c-Cbl dependent manner [11,12,30]), but these studies did not examine tumor initiation or consequences of Cdc42 knockdown on sensitivity to therapeutic agents. In addition, recent studies on GBM cells isolated and grown in conditions that do not select for TICs raise the possibility that c-Cbl also may be inhibited by transglutaminase-2 [31].…”
Section: Discussionmentioning
confidence: 99%
“…AIP4 Binds to the CIN85 Scaffolding Protein-The ␤PIX-SH3 domain is phylogenetically similar to the three SH3 domains of CIN85, an adaptor protein involved in Cbl-mediated downregulation of RTKs (9,26). Like ␤PIX, the SH3 domains of CIN85 recognize and bind the non-canonical PXXXPR motifs in Cbl and PAK proteins (26,28,39).…”
Section: Resultsmentioning
confidence: 99%
“…Like ␤PIX, the SH3 domains of CIN85 recognize and bind the non-canonical PXXXPR motifs in Cbl and PAK proteins (26,28,39). When both FLAG-tagged CIN85 and Myc-tagged AIP4 were co-expressed in HEK293T cells we found that CIN85 pulled down AIP4, albeit to a lesser extent than ␤PIX (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation